2016
DOI: 10.1186/s12885-016-2831-y
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin mediates caspases activation and induces apoptosis through P38 and JNK MAPK pathways in human renal carcinoma

Abstract: BackgroundRenal cell carcinoma (RCC) is one of the tumors most refractory to chemotherapy to date. Therefore, novel therapeutic agents are urgently needed for this disease. Capsaicin (CPS), a natural active ingredient of green and red peppers, and a ligand of transient receptor potential vanilloid type 1 (TRPV1), has been showed potential in suppression of tumorigenesis of several cancers. Nonetheless, the anti-cancer activity of CPS has never been studied in human RCC.MethodsCCK8 analysis, LDH release activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 37 publications
4
35
0
Order By: Relevance
“…Inhibition of the JNK pathways in cardiomyocytes results in attenuated hypertrophic growth induced by agonist stimulation (28). In addition, previous studies have demonstrated that the activation of JNK is involved in the induction of the inflammatory response and apoptosis (29,30). The present study revealed that DIM inhibited the phosphorylation of JNK in hypoxia-induced H9c2 cells, which indicated that the anti-apoptosis effect of DIM may mediated by blocking JNK pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Inhibition of the JNK pathways in cardiomyocytes results in attenuated hypertrophic growth induced by agonist stimulation (28). In addition, previous studies have demonstrated that the activation of JNK is involved in the induction of the inflammatory response and apoptosis (29,30). The present study revealed that DIM inhibited the phosphorylation of JNK in hypoxia-induced H9c2 cells, which indicated that the anti-apoptosis effect of DIM may mediated by blocking JNK pathway.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, the p-JNK levels were significantly elevated after treatment with 250 µM capsaicin, which was correlated with the capsaicin-induced apoptotic effects in all 3 OS cell lines; these data suggest that capsaicin-induced OS cell apoptosis is at least partially involved in activating the JNK signaling pathway. Our results are consistent with those of previous findings that capsaicin could increase JNK phosphorylation and thus promote apoptosis in cancer cells ( 41 , 47 ). Taken together, the findings in the present study strongly suggest that inactivation of ERK1/2 and p38 plays an important role in capsaicin-induced inhibition of proliferation and cell cycle arrest in OS cells, whereas JNK activation participated in capsaicin-induced apoptosis.…”
Section: Discussionsupporting
confidence: 94%
“…The MAPK family plays a critical role in OS cell survival, proliferation and angiogenesis. In addition, some other studies showed that capsaicin could alter the MAPK pathways in cancer cells ( 25 , 41 ). Based on previous studies, we hypothesized that capsaicin may mediate its anti-OS effects by regulating MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between TRPV1 channel expression and patients with glioblastoma multiforme was also reported (Alptekin et al 2015). Involvement of TRPV1 activation on the tumor cell proliferation and ROS production in several cancer types was recently reported (Qian et al 2016;Liu et al 2016). In addition, antioxidant treatments via inhibition of the TRPV1 in the cancer cells decreased oxidative stress (Qian et al 2016;Liu et al 2016).…”
Section: Research Articlementioning
confidence: 87%